2016
DOI: 10.5430/ijba.v7n6p96
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure: The Evidence from European Energy Companies

Abstract: The main aims of this study are to determine the factors which affect capital structure of corporations operating in energy sector and to detect capital structure theories with which capital structure of energy sector companies would comply. In this context, a panel data analysis was performed on totally 79 European energy companies operated between the years 2009 -2012. According to results of the study; diminishing leverage rate caused by increased liquidity in European energy companies can be explained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 26 publications
4
24
0
9
Order By: Relevance
“…Therefore, firms prefer to issue equity as the cost of equity is typically cheaper than debt. Several studies confirmed that assets tangibility has a positive relationship with leverage level which is in line with the Trade-off theory (Berkman, Iskenderoglu, Karadeniz, & Ayyildiz, 2016;Deesomsak, Paudyal, & Pescetto, 2004;Dhingra & Dev, 2016;Hussain et al, 2015;Md-Yusuf, Mohammad Yunus, & Md Supaat, 2013;Sabir & Malik, 2012;Vo, 2017). Matias and Serrasqueiro (2017), Vo (2017), Chipeta and Deressa (2016), Oino and Ukaegbu (2015), Proença, Laureano, and Laureano (2014), Taddese Lemma and Negash (2013), Ting and Lean (2011) showed evidence that assets tangibility has a positive relationship with long-term debt as posited by Trade-off theory, and it has a negative relationship with short-term debt as posited by Pecking Order theory.…”
Section: Tangibilitysupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, firms prefer to issue equity as the cost of equity is typically cheaper than debt. Several studies confirmed that assets tangibility has a positive relationship with leverage level which is in line with the Trade-off theory (Berkman, Iskenderoglu, Karadeniz, & Ayyildiz, 2016;Deesomsak, Paudyal, & Pescetto, 2004;Dhingra & Dev, 2016;Hussain et al, 2015;Md-Yusuf, Mohammad Yunus, & Md Supaat, 2013;Sabir & Malik, 2012;Vo, 2017). Matias and Serrasqueiro (2017), Vo (2017), Chipeta and Deressa (2016), Oino and Ukaegbu (2015), Proença, Laureano, and Laureano (2014), Taddese Lemma and Negash (2013), Ting and Lean (2011) showed evidence that assets tangibility has a positive relationship with long-term debt as posited by Trade-off theory, and it has a negative relationship with short-term debt as posited by Pecking Order theory.…”
Section: Tangibilitysupporting
confidence: 73%
“…Liquidity is the ability of an asset to be converted directly into cash without affecting the asset's price to meet short-term needs under a specified acute stress scenario and without the need to readjust basic capital structure (Berkman et al, 2016;Md-Yusuf et al, 2013;Saarani & Shahadan, 2013). Highly liquid assets will ensure positive working capital, and therefore fund can be saved for future long-term investment without the need to borrow from other external sources.…”
Section: Liquiditymentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Sofat & Singh (2017) pada perusahaan manufaktur di India menunjukkan hasil bahwa struktur aktiva berpengaruh positif dan signifikan dengan struktur modal perusahaan. Hasil tersebut kemudian didukung oleh penelitian yang dilakukan oleh M'ng et al (2017), Nnadi (2016), Berkman et al (2016), dan Gwatidzo et al (2016) yang juga menunjukkan hasil positif dan signifikan antara struktur aktiva dan struktur modal perusahaan. Namun hasil lain ditemukan oleh Acaravci (2015), Alipour et al (2015) dengan hasil yang menunjukkan pengaruh negatif dan signifikan antara struktur aktiva dan struktur modal perusahaan.…”
Section: Pendahuluanunclassified
“…With considerable current assets, the company will choose to fund its business activities from internal funding. It is found that there is a negative relationship between liquidity and capital structure [14], [19], [25]- [28]. Nevertheless, trade-off theory believes that a positive relationship between capital structure and liquidity because higher liquidity ratio can support a relatively higher debt ratio due to a higher ability of a firm to satisfy short-term contractual obligations on time.…”
Section: A Firm Sizementioning
confidence: 99%
“…Research conducted by Akinlo [15]states that the level of corporate liquidity has a positive effect on capital structure. However, some other studies revealed that liquidity has negatively affectedcapital structure [14], [19], [25]- [28]. Some previous studies also revealed that growth opportunities have a positive effect on capital structure [8], [14], [16], [18], [21], [29], but others indicated negative effect [15], [22], [30].…”
Section: Introductionmentioning
confidence: 99%